Literasi Budaya untuk Siswa Thailand: Memperkenalkan Kekayaan Intelektual Komunal Indonesia - Disemadi, Hari Sutra; Andarini, Retno (Yayasan Abdurrauf Cendekia Nusantara, 2024)
Many Indonesians, especially young people, are not familiar with their own regional cultures and traditions. This lack of knowledge poses a significant threat to the continuity of Indonesian culture and traditions, as it makes them more vulnerable to claims from other countries. As a preventive measure, an educational initiative was conducted for Thai students. This education was delivered through a legal awareness program aimed at providing a deep understanding of the importance of protecting culture and traditions as communal intellectual property. The implementation of this legal awareness program yielded diverse results. Some participants were able to grasp the importance of protecting culture and traditions as communal intellectual property, while others faced difficulties understanding the material due to language barriers. Nevertheless, the overall outcome of the activity was successful in raising awareness about the importance of preserving Indonesian culture and traditions and providing Thai students with new insights into Indonesia's legal efforts to protect these cultural assets. Abstrak: Masih banyak masyarakat Indonesia, terutama anak muda, yang tidak mengetahui budaya dan tradisi dari daerahnya sendiri. Ketidaktahuan ini berpotensi menjadi ancaman besar terhadap keberlanjutan budaya dan tradisi Indonesia, karena dapat mempermudah klaim dari negara lain. Sebagai upaya preventif, dilakukan edukasi mengenai budaya dan tradisi kepada siswa Thailand. Metode pelaksanaan edukasi ini melalui penyuluhan hukum yang bertujuan untuk memberikan pemahaman mendalam mengenai pentingnya perlindungan budaya dan tradisi sebagai kekayaan intelektual komunal. Pelaksanaan penyuluhan hukum ini memberikan hasil yang beragam. Beberapa peserta mampu memahami arti penting perlindungan budaya dan tradisi sebagai kekayaan intelektual komunal, sementara yang lain mengalami kesulitan memahami materi karena kendala bahasa. Meskipun demikian, kegiatan ini secara keseluruhan berhasil meningkatkan kesadaran tentang pentingnya melestarikan budaya dan tradisi Indonesia, serta memberikan wawasan baru kepada siswa Thailand mengenai upaya perlindungan hukum yang dilakukan oleh Indonesia.